Field and greenhouse evaluations of soil suppressiveness to Heterodera glycines in the Midwest corn-soybean production systems - Hu, Weiming (J Nematol, 2019)
Soil suppressive to the soybean cyst nematode (SCN), a major yield-limiting pathogen of soybean, plays an important role in biological control. Field and greenhouse experiments were conducted to evaluate the effects of tillage, crop sequence, and biocide application on SCN suppression in corn-soybean cropping systems in Minnesota. The experiment was a split-plot design with no-tillage and conventional tillage as main plots, and six crop-biocide treatments (CRCS, CSCS, SSSS, SSSS + streptomycin, SSSS + captan, and SSSS + formaldehyde – the four letters represent crops in 2009 to 2012, respectively; C is corn, R is SCN-resistant soybean, and S is SCN-susceptible soybean) as subplots with four replicates. Soil samples were taken from each plot at planting, midseason, and harvest each year for SCN egg counts, and soybean yield was determined. In addition, soil samples collected from each plot at midseason were assayed for suppressiveness to SCN. Tillage had minimal effect on SCN population density and soybean yield. Annual rotation with corn reduced SCN population density, but also reduced soil suppressiveness as SCN egg population density increased in the following SCN-susceptible soybean compared with soybean monoculture. Rotation with SCN-resistant soybean and corn was the most effective in reducing SCN population density. The bactericide streptomycin did not affect SCN populations but the fungicide captan increased SCN population density. The biocide formaldehyde was the most effective in reducing the level of suppressiveness to SCN. The greenhouse study confirmed that the soil was suppressive to SCN, but failed to detect effects of tillage, crop sequence, and biocide field treatments. This study demonstrated that the soil in the fields was suppressive to the SCN, and biological agents, especially fungal antagonists, were involved in nematode suppression.